IMPLEMENTATION OF POLICY STRATEGIES TO FULFILL GUIDING BLOCKS FOR BLIND PEOPLE WITH DISABILITIES IN MEDAN CITY - Natasya Pebiani Marbun; Wiro Oktavianur Ginting (Yayasan Wayan Marwan Pulungan, 2025)
This study aims to determine the Implementation of the Guiding Block Fulfillment Policy Strategy for Persons with Blind Disabilities in Medan City. This research uses a qualitative descriptive approach with data collection techniques namely interviews, observation and documentation. According to Bhat (2000) there are 4 (four) criteria that must be owned, namely: security, convenience, comfort and aesthetics. The results of this study use 4 indicators, namely the security that exists on the guiding block after the construction of public facilities for people with disabilities has not shown a level of security for users, especially blind people with disabilities. Second, convenience has provided convenience for people with disabilities because it can help them in carrying out activities outside the environment. Third, comfort does not provide comfort to persons with disabilities due to the lack of supervision and socialization to ordinary people regarding the use of guiding block facilities provided by the government for persons with disabilities, aesthetics in this case has not shown aesthetic value on guiding blocks that have been built in Medan City because there are still many guiding blocks that have damaged roads. To achieve an inclusive environment and create a disability-friendly city, efforts must begin with the way the government must involve people with disabilities themselves and socialize to all communities about the function of guiding block construction so that they can find out whether the development carried out can provide direct benefits to users of public facilities..